Inclusion and Technology: A Cultural Journey From Hearing Loss - Aragón García, Maribel; Bustos Farías, Eduardo; Flores Mendoza, Yaxkin (Journal of Strategic Innovation and Sustainability, 2023)
Mexico’s fusion between inclusion, culture, and technology has been undervalued. Despite multiple attempts to include people with hearing loss in various cultural spaces, technology is not exploited to reach them. The objective was to design and validate a mobile application that explains a mural through a 3D animation using Lenguaje de Señas Mexicano, (Mexican Sign Language, LSM) so that people with hearing loss do not have to depend on someone to understand the information. The waterfall methodology was used, and each part was created sequentially. As a result, the acceptance of the project reflected the need for technological solutions that support the reality faced by people with hearing loss. The work shows that it is possible to contribute to the reality of those living with disabilities. This proposal is a precedent to begin studies and developments based on the day-to-day experience of the public, whose quality of life is to be improved.